3D Graphene Oxide Micropatterns Achieved by Roller‐Assisted Microcontact Printing Induced Interface Integral Peel and Transfer. Issue 3 (1st December 2016) - Xiao, Peng; Du, Shiyu; Zhang, Tao; Qiu, Nianxiang; Zhang, Jiawei; Huang, Youju; Wan, Changjin; Jordan, Rainer; Huang, Qing; Liu, Zhaoping; Chen, Tao
Abstract : Most fascinating applications of graphene‐based devices are highly dependent on the precise fabrication of patterned graphene microstructures. While considerable progress of 2D patterning of graphene has been achieved with various lithographic techniques, the realization of patterned 3D graphene microstructures still remains a significant challenge. Here, a rapid and highly scalable roller‐assisted microcontact printing (RAμCP) strategy for the fabrication of 3D graphene oxide micropatterns is reported. The facile RAμCP allows for the robust negative duplication of 3D topologies of the microstructured stamp using chemically modified graphene as the inks. The patterned 3D graphene microstructures exhibit interesting properties of graphene itself and allow for further functionalization of polymers to enable the potential integration of the 3D patterned microstructures into next‐generation 2D Janus hybrid thin film for chemical sensors and other electronic devices. Abstract : 3D graphene oxide microarchitectures are duplicated from the designed poly(dimethylsiloxane) mold at a low cost though the interface integral peel and transfer, which is named after roller‐assisted microcontact printing (RAμCP). As a rapid and highly scalable surface patterning new technique, RAμCP can be expanded to fabricate other 3D patterned microstructures.